An Exploratory Modelling Study on Late Pleistocene Mega-Tsunamis Triggered By Giant Submarine Landslides in the Mediterranean - JM Abri; Raul Perianez (Annals of Limnology and Oceanography - Peertechz Publications, 2017)
Gigantic submarine landslides are among the most energetic events on the Earth surface. During the Late Pleistocene the Mediterranean Sea was the scenario of a 9 number of such events, some of whose  geological fingerprints are the 500 km3 mass transport deposit SL2 at the Nile delta fan (dated at ca. 110ka BP) and the Herodotus Basing Mega turbidite (HBM, a 400 km3 deposit dated at ca. 27.1 ka BP).  This paper presents an exploratory study on the tsunamigenic potential of these slides by using a numerical model based on the 2D depth-averaged non-linear barotropic shallow water equations. The sliding mass is modelled both as a rigid block with a prescribed motion and as a viscous fl ow layer. The 26 km3 debris fl ow BIG'95 scenario (at the Ebro continental slope, 11.5 ka BP) served for model comparison against independent modelling works. Based upon the available geologicalstudies, several source scenarios have been modelled. Our results show that the generated tsunamis would have had up to hundred fold the peak energy of some extreme historical ones, such as the 1755 Lisbon tsunami. Thus, the HBM tsunami could have reached peak energies over one hundred Megatons, producing runups over 50 m height along some 1300 km2 of shoreline in the eastern Mediterranean. The study also comprises their propagation pattern, their impacts along the former shoreline and their energy partitioning. The highest tsunami energies were associated to thick landslides at shallow depths, with high slope angles and within a gulf geometry.